2014
DOI: 10.1002/adfm.201304156
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Stabilized Sulfur‐Microporous Carbon Cathodes for Li–S Batteries

Abstract: 4156www.MaterialsViews.com wileyonlinelibrary.com interact with two Li atoms per S atom, the S cathode can provide reversible high capacity of 1675 mAh g -1 at average potentials of 2.0 V, [1][2][3] which is 10× higher energy density than that of classical commercial LiCoO 2 cathode. Since the capacity of current LiCoO 2 -graphite Li-ion battery is controlled by LiCoO 2 cathode, replacement of expensive LiCoO 2 with cheap S will largely enhance the battery energy density. However, the S cathodes are still suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
150
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(158 citation statements)
references
References 55 publications
8
150
0
Order By: Relevance
“…The second step is similar to those reported in C-Cu-S composites synthesized by a chemical reaction between Cu and S, which are attributed to strong chemical bonding between S and Cu. 19,20 The delay in extracting S from the electrode confirms the occurrence of chemical bonds between sulfur and Cu current collector through copper sulfides. Additionally, the temperature ranges of weight loss for the sulfur electrode on Cu are evidently different from those of the mixtures of Cu and S powders with 2:1 and 1:1 molar ratios, which suggests that Cu 2 S and CuS are already formed at 50…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second step is similar to those reported in C-Cu-S composites synthesized by a chemical reaction between Cu and S, which are attributed to strong chemical bonding between S and Cu. 19,20 The delay in extracting S from the electrode confirms the occurrence of chemical bonds between sulfur and Cu current collector through copper sulfides. Additionally, the temperature ranges of weight loss for the sulfur electrode on Cu are evidently different from those of the mixtures of Cu and S powders with 2:1 and 1:1 molar ratios, which suggests that Cu 2 S and CuS are already formed at 50…”
Section: Resultsmentioning
confidence: 99%
“…The same CV behavior with a large overpotential in the first reduction process is also reported in a Li/S cell with a high S loading, which results from the large strain/stress due to large volume change. 20 The relatively stable cathodic and anodic current peaks in the following scans demonstrate the cycling stability of the S cathode in the nucleophilic electrolyte.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion of the dissolved polysulfides between the Li anode and cathode leads to shuttle between the two electrodes, 3,4 which may cause the loss of active materials, low coulombic efficiencies and poor cyclability of Li-S batteries. 5 Recent studies have shown that a metal can stabilize sulfur through chemical bonding 6 and its metallic porous nanostructure can suppress the shuttle effect 7 to attain the excellent coulumbic efficiency and cyclability. Based on the reactivity with sulfur, 8 three-dimensional architecture and good electronic conductivity of nickel foam, 9-11 here we present a sulfur-nickel foam cathode material for Li-S batteries.…”
mentioning
confidence: 99%
“…Recent studies have shown that a metal can stabilize sulfur through chemical bonding 6 and its metallic porous nanostructure can suppress the shuttle effect 7 to attain the excellent coulumbic efficiency and cyclability. Based on the reactivity with sulfur, 8 three-dimensional architecture and good electronic conductivity of nickel foam, 9-11 here we present a sulfur-nickel foam cathode material for Li-S batteries.…”
mentioning
confidence: 99%